2009
DOI: 10.1111/j.1439-0388.2008.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters and genome scan for 15 semen characteristics traits of Holstein bulls

Abstract: A QTL detection experiment was performed in French dairy cattle to search for QTL related to male fertility. Ten families, involving a total of 515 bulls, were phenotyped for ejaculated volume and sperm concentration, number of spermatozoa, motility, velocity, percentage of motile spermatozoa after thawing and abnormal spermatozoa. A set of 148 microsatellite markers were used to realize a genome scan. First, genetic parameters were estimated for all traits. Semen production traits were found to have moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
97
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 21 publications
17
97
3
1
Order By: Relevance
“…Previous studies were performed by whole genome analysis using microsatellite markers to determine Quantitative Trait Loci (QTLs) (Druet et al, 2009). This group found two QTLs for semen volume on chromosomes 22, the same which we found for our most significant SNPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies were performed by whole genome analysis using microsatellite markers to determine Quantitative Trait Loci (QTLs) (Druet et al, 2009). This group found two QTLs for semen volume on chromosomes 22, the same which we found for our most significant SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on bull's semen refer to quality traits like motility and morphological abnormalities of sperm (Druet et al, 2009). Indeed, these traits have key value in assessing semen in AI companies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work done under collaboration between UNCEIA, INRA PRC Nouzilly and GABI allowed to identify several chromosomal regions associated with such variables [26].…”
Section: Qtl Fine Mapping and Accuracy Of Phenotyping For Fertility Tmentioning
confidence: 99%
“…So far, some QTL associated with sperm quality were detected in bulls (Druet et al, 2009) and boars Xing et al, 2009), and also some candidate genes are considered to be associated with male animal fertility traits, such as swine actin (Wimmers et al, 2005;Lin et al, 2006) and murine Capza3 (Geyer et al, 2009). Our previous findings showed that some bulls with numerous linked mutations in the FSHB gene, including 13 substitutions and 1 insertion in the upstream regulation region (5ꞌ-URR) and the coding region of exon 3, exhibited slightly lower serum FSH concentration, poor-quality semen, and low fertility (Dai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%